Utilization of Test and Non-Test Instruments in Guidance and Counseling - Rober Sandra; Nurfarhanah; Zadrian Ardi (Journal Of Psychology, Counseling And Education, 2025)
The use of test and non-test instruments in guidance and counseling services is a crucial aspect in understanding the needs, potential, and problems of students comprehensively. The urgency of this study lies in the need to strengthen the practice of assessment in the midst of the dynamic needs of students in the current era. This study aims to systematically review the utilization of test and non-test instruments in counseling services based on national and international journal articles. The method used is a literature review with a qualitative-descriptive approach, through content analysis of published publications. The results show that the combined use of test and non-test instruments can improve assessment accuracy, but its implementation still faces methodological and practical challenges. This study contributes to formulating strategies for strengthening guidance and counseling assessment based on valid and relevant data, and recommends developing the competence of guidance and counseling teachers in assessment.